2018
DOI: 10.6018/riite/2018/342681
|View full text |Cite
|
Sign up to set email alerts
|

Integración de las TIC en los procesos de enseñanza-aprendizaje de la especialidad de Pedagogía en los conservatorios superiores de música

Abstract: Esta investigación analiza la integración de Tecnologías de la Información y la Comunicación (TIC) en los procesos de enseñanza-aprendizaje de los futuros pedagogos de música. Para ello se ha tomado en consideración la perspectiva del profesorado de los departamentos de Pedagogía de 14 conservatorios superiores españoles. Los datos se han recogido a partir de un cuestionario y un grupo de discusión. En general la predisposición a utilizar las TIC es alta, pero se basa en criterios de acceso a recursos y eficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…As of today, Music Education in the 21st century must cater to contemporary music competencies associated with technologies so that they promote new skills and abilities in this area; for example, the development of musical thinking. Similarly, through their use, new didactic, methodological, and pedagogic approaches must be created that is centered on the active participation of students so that they feel more motivated by music learning in a continuous manner [41,43,46,48,50,51]. This is possible because the use of EdTech allows one to work in a continuous manner through time and anywhere one wishes, as smartphones, among others, allow one to connect instantaneously.…”
Section: Notionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of today, Music Education in the 21st century must cater to contemporary music competencies associated with technologies so that they promote new skills and abilities in this area; for example, the development of musical thinking. Similarly, through their use, new didactic, methodological, and pedagogic approaches must be created that is centered on the active participation of students so that they feel more motivated by music learning in a continuous manner [41,43,46,48,50,51]. This is possible because the use of EdTech allows one to work in a continuous manner through time and anywhere one wishes, as smartphones, among others, allow one to connect instantaneously.…”
Section: Notionmentioning
confidence: 99%
“…Other aspects that should be considered are the existing music pedagogies; given that we cannot forget about the pedagogies that are nurtured by current learning: Dalcroze, Martenot, Orff, Willems, Kodály, Suzuki, Tonic Sol-Fa, Montessori, Paynter, Maurice Chevais, Schafer, Soundcheck, and which come from the 20th century, being considered as active methodologies. Likewise, and with respect to the characteristics, the authors write that the teachers must know the essential and main characteristics that the technological tools have to be able to correctly apply them within the class group, as it is primordial to deepen into the acquisition of knowledge [40,41,54,86,90,100].…”
Section: Characterizationmentioning
confidence: 99%
“…In respect to other educational spheres, the specific context of teaching in music conservatories and schools of music shows greater resistance to incorporating pedagogical innovations related to the new technologies (Díez-LATORRE, 2018). In his study on the integration of ICTs in conservatories of music in the Spanish region of Galicia, Belló (2012) found that the use of educational technologies was scarce, due to a low level of motivation, as well as lack of time and training of teachers.…”
Section: Digital Competence In the Field Of Teaching In Music Conserv...mentioning
confidence: 99%
“…Evidentemente la escuela debe favorecer que las TIC se integren en las aulas, ya que benefician la alfabetización digital, son fuente de información, facilitan los procesos de enseñanza-aprendizaje, rompen las barreras espacio-temporales, son elementos motivadores y promueven la creatividad (Belloch, 2012;Ferro, Martínez y Otero, 2009;Marqués, 2012;Román, Chao-Fernández y Mato-Vázquez, 2018). Indudablemente, el avance tecnológico en su compromiso de rediseñar el acto educativo hacia una educación 2.0, provoca que dentro de los diferentes entornos educativos surjan nuevos espacios de aprendizaje y replanteamientos en la pedagogía musical (Cabero y Barroso, 2013;Area y Ribeiro, 2012), pero el docente debe ser consciente de que, si las TIC no se emplean adecuadamente, no serán efectivas (Díez y Carrera, 2018;Valcárcel y González, 2013).…”
unclassified